Is gender in the eye of the beholder? Identifying cultural attitudes with art auction prices - Renée Adams; Roman Kräussl; Marco Navone; Patrick Verwijmeren (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
In the secondary art market, artists play no active role. This allows us to isolate cultural influences on the demand for female artists' work from supply-side factors. Using 1.5 million auction transactions in 45 countries, we document a 47.6% gender discount in auction prices for paintings. The discount is higher in countries with greater gender inequality. In experiments, participants are unable to guess the gender of an artist simply by looking at a painting and they vary in their preferences for paintings associated with female artists. Women's art appears to sell for less because it is made by women.
urn:nbn:de:hebis:30:3-469276
Keywords: Z11; J16; D44; 330; Art; Auction; Gender; Culture; Bias